Adaptation, anticipation-bias and optimal income taxation - Thomas Aronsson; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2012)
Adaptation is omnipresent but people systematically fail to correctly anticipate the degree to which they adapt. This leads individuals to make inefficient intertemporal decisions. This paper concerns optimal income taxation to correct for such anticipation-biases in a framework where consumers adapt to earlier consumption levels through a habit-formation process. The analysis is based on a general equilibrium OLG model with endogenous labor supply and savings where each consumer lives for three periods. Our results show how a paternalistic government may correct for the effects of anticipation-bias through a combination of time-variant marginal labor income taxes and savings subsidies. Furthermore, the optimal policy mix remains the same, irrespective of whether consumers commit to their original life-time plan for work hours and savings decided upon in the first period of life or re-optimize later on when realizing the failure to adapt.
Keywords: D03; D61; D91; H21; 330; optimal; taxation; adaptation; habit-formation; anticipation-bias; paternalism; Optimale Besteuerung; Einkommensteuer; Konsumtheorie; Zeitpräferenz; Anpassung; Erwartungstheorie; Bias; Theorie